Appraisals Analysis on the Argumentation Structure of Indonesian Undergraduate Students’ Research Articles - Reddy, Alfa Lisa Muslimah Febriyanti; Pradita, Intan (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
This research aims to analyze the argument structure of undergraduate students’ research articles that focus on the introduction section. The data collection was conducted by analyzing the proceedings in the "Background" section written by undergraduate students at university in Indonesia. The data were then analyzed by using a corpus. This research found type of argument of this study were proclaim, disclaim, entertain, and attribute. The lexical choice that was used proclaim with a total of 46. The lexemes entertain a total of 37. The next lexical choice that was used is disclaim with a total of 33. Finally, attribute a total of 26 as the lowest engagement in appraisal.